Pengaruh transformational leadership dan self efficacy terhadap job performance melalui employee engagement (studi kasus sektor publik di pemerintahan Kabupaten Jember) - Paleva, Fenza Gusti Naufal; Handriyono; Gusminto, Eka; Susanto, Arnis Budi (Jurnal Ilmu Manajemen, 2024)
Humans are the main axis in the company's progress, so good and qualified human resources are needed to achieve an agency's vision, mission and goals. Based on the observations, several phenomena were found related to job performance in the research object, namely the Jember Regency Public Sector Government, and several variables were considered influential. This research aims to determine and analyse whether transformational leadership and self-efficacy influence job performance through employee engagement (Case Study in the Public Sector of Jember Regency Government). This research design is explanatory research. The population in this study was 213 employees. The data sources used are primary data obtained directly in the field, such as interviews, observations and questionnaires, and secondary data obtained from literature studies through journals and documentation. The data analysis method in this research uses Partial Least Square (PLS) analysis with SmartPLS 4.0 software. The results of this research show that 1) transformational leadership influences employee engagement, 2) self-efficacy influences employee engagement, 3) transformational leadership influences job performance, 4) self-efficacy influences employee job performance, 5) employee engagement influences employee job performance, 6) transformational leadership influences employee job performance through employee engagement, 7) self-efficacy influences employee job performance through employee engagement.